2020
DOI: 10.1108/ijopm-12-2020-833
|View full text |Cite
|
Sign up to set email alerts
|

The hidden side of sustainable operations and supply chain management: unanticipated outcomes, trade-offs and tensions

Abstract: PurposeThe research is based on a critically analyzed literature review focused on the unanticipated outcomes, trade-offs and tensions of sustainable operations and supply chain management (OSCM), including the articles selected for this special issue.Design/methodology/approachThe authors introduce the key concepts, issues and theoretical foundations of this special issue on “The hidden side of sustainable operations and supply chain management (OSCM): Unanticipated outcomes, trade-offs and tensions”. The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
73
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(80 citation statements)
references
References 118 publications
4
73
0
3
Order By: Relevance
“…Our case study has established how the original accident itself could have been directly or indirectly avoided by the ship's organisation, notably by co-ordinating with or responding to the relevant authorities (port authorities and coast guard). Our case study showed that consistent with the literature, much of the formal institutional stakeholder decision-making focused on economic interests, which led to (un)anticipated consequences related to negative social and environmental factors (Matos et al, 2020). It also shows the catastrophic domino effect deriving from poor decision-making subsequent to the initial accident (SE2-4), all of which might have been avoided had there been a shared understanding of the situation, based on multimedia information collated from the different institutional and noninstitutional stakeholders.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our case study has established how the original accident itself could have been directly or indirectly avoided by the ship's organisation, notably by co-ordinating with or responding to the relevant authorities (port authorities and coast guard). Our case study showed that consistent with the literature, much of the formal institutional stakeholder decision-making focused on economic interests, which led to (un)anticipated consequences related to negative social and environmental factors (Matos et al, 2020). It also shows the catastrophic domino effect deriving from poor decision-making subsequent to the initial accident (SE2-4), all of which might have been avoided had there been a shared understanding of the situation, based on multimedia information collated from the different institutional and noninstitutional stakeholders.…”
Section: Discussionsupporting
confidence: 78%
“…We show how current communication is largely bilateral within the ship's organisation, consisting of the insurers, ship owners and the ship's captain. As such, many of the critical decisions related to the accident were taken in a vacuum, lacked transparency and were driven by tensions and trade-offs, including competing economic interests (Matos et al, 2020). Our analysis shows that these delays and decisions led to irreversible economic, social and ecological consequences, which could have been avoided.…”
Section: Introductionmentioning
confidence: 93%
“…Social sustainability practices help the organization to achieve a greater social reputation (Hong et al, 2012;Marshall et al 2015;Kauppi and Hannibal, 2017), whilst from an economic perspective of sustainability, Woolworths Company saved 9.3 million US Dollars after focusing on ecological, social, and economic indices, based on the triple bottom line initiative (Santos et al 2014). Matos et al (2020Matos et al ( , p. 1750) argue that the entire globe is facing unprecedented challenges in the form of "climate change, deforestation, biodiversity loss, inequality, famine, labor exploitation, modern slavery, and more recently global pandemics". On the other hand, consumers and key stakeholders are expecting organizations to be more responsible towards their contribution to minimizing environmental degradation (Wilhelm et al 2016;Matos et al 2020).…”
Section: Sustainabilitymentioning
confidence: 99%
“…Matos et al (2020Matos et al ( , p. 1750) argue that the entire globe is facing unprecedented challenges in the form of "climate change, deforestation, biodiversity loss, inequality, famine, labor exploitation, modern slavery, and more recently global pandemics". On the other hand, consumers and key stakeholders are expecting organizations to be more responsible towards their contribution to minimizing environmental degradation (Wilhelm et al 2016;Matos et al 2020). The pandemic crisis resulting from COVID-19 has further increase awareness of environmental and social sustainability amongst consumers (He and Harris, 2020;Sarkis, 2021;Severo et al 2021).…”
Section: Sustainabilitymentioning
confidence: 99%
“…We have seen many calls for OSCM scholars to increase the relevance of their research (Van Wassenhove, 2019) and undertake studies that are practice-based and responsible (Lee and Tang, 2018), contributing toward more sustainable and resilient supply chains (Sarkis, 2021), but accounting for difficult trade-offs (Matos et al, 2020). The continuing problem of drug shortages demands that the OSCM community gets more involved and provides us with a great opportunity: (1) the problem has substantial patient and economic impacts; (2) it poses complex questions for stakeholders to which there is no obvious answer; (3) OSCM scholars are well positioned to address these questions; and (4) the problem introduces fundamentally new research directions for OSCM and pushes the frontiers of our discipline.…”
Section: Final Remarksmentioning
confidence: 99%